Caesarean section by maternal age group among singleton deliveries and primiparous Japanese women: a secondary analysis of the WHO Global Survey on Maternal and Perinatal Health. Issue 1 (December 2016) - Yoshioka-Maeda, Kyoko; Ota, Erika; Ganchimeg, Togoobaatar; Kuroda, Mariko; Mori, Rintaro
Abstract Background The rising caesarean section rate is an important public health concern that in turn increases maternal and perinatal risks of adverse effects, unnecessary medical consumption, and inequities in worldwide access. The aim of this study was to investigate caesarean section indications by maternal age group and examine the association between age and caesarean section in primiparous Japanese women with singleton births. Methods We analyzed the Japanese data of primiparous women with singleton births from the WHO Global Survey on Maternal and Perinatal Health to compare maternal and neonatal characteristics and outcomes between groups with and without caesarean section. Women were divided into 3 maternal age groups (≤29, 30 to 34 and ≥35 years). We performed multivariable logistic-regression analysis to identify characteristics associated with caesarean section. Results Of the 3245 women with singleton births were included in the Japanese data, 610 women (18.8 %) delivered by caesarean section, half of whom (n = 305) were nulliparous. We included singleton nulliparous women (1747 deliveries) in our analysis. The maternal age 35 years old was associated with higher risks for all caesarean section (adjusted odds ratio [AOR] 1.89, 95 % CI 1.28–2.78) and emergency antepartum caesarean section (AOR 2.26, 95 % CI 1.49–3.40). Intrapartum caesarean section, which is mainly performed for obstetric indications, was not higher among the older maternal age group. Conclusion In Japan, advanced maternal age significantly increased the risk for caesarean section; however, intrapartum caesarean section was not higher risk among the older age group. Management of maternal complications would help to reduce the rate of caesarean sections and associated unnecessary medical consumption.